OPTIMIZING LEARNING: A META-ANALYSIS OF TIME MANAGEMENT STRATEGIES IN UNIVERSITY EDUCATION - Liu, Da (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Effective time management skills are essential for academic success in university education. However, the literature lacks a comprehensive synthesis of time management strategies across diverse academic disciplines and the effectiveness of innovative teaching methods in promoting these skills. This meta-analysis aims to address this gap by systematically synthesizing empirical evidence from a wide range of scholarly sources, including peer-reviewed journals, conference proceedings, and educational reports, to provide a nuanced understanding of the significance of time management in university education. Grounded in established theoretical frameworks such as the Time Management Behavior Theory and the Goal Setting Theory, this study offers a robust theoretical foundation for examining the interplay between time management strategies, academic performance outcomes, and pedagogical approaches in tertiary education settings. Variables and Conceptual Framework: Key variables under scrutiny include various time management interventions, academic performance metrics, and pedagogical innovations. The conceptual framework integrates principles from cognitive load theory and self-regulated learning to elucidate the mechanisms through which time management strategies influence student learning outcomes. Employing a meta-analysis approach, this study systematically synthesizes quantitative data from previous research to identify patterns, trends, and effect sizes. Meta-regression techniques are applied to explore potential moderating variables, while thematic analysis is used to extract common themes and best practices across different academic contexts. Findings and Conclusions: The meta-analysis reveals compelling evidence of a positive correlation between effective time management strategies and improved academic performance across diverse academic disciplines. Furthermore, innovative teaching methodologies that integrate time management principles into course curricula are found to significantly enhance student engagement, motivation, and overall learning outcomes. In light of these findings, the study advocates for the widespread adoption of tailored pedagogical approaches aimed at cultivating time management skills among university students, thereby empowering them to navigate the complexities of higher education successfully. This abstract provides a detailed overview of the study’s background, literature gap, theoretical framework, variables, methodology, findings, and conclusions, emphasizing the use of meta-analysis as the primary methodological approach.